ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi pada PT. Kereta Api Indonesia Daop IV Semarang) - Petra Surbakti, Marwan; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2013)
The research was conducted in PT.KAI Daop IV Semarang, the government-owned services company, formerly known as low standard employee performance. This is reflected in some indicator like ticket scalpers, either at the station Poncol and Tawang, lack of service, ticketing is less representative, lack of employee commitment to serving customers, work culture is individualistic in office, lack of employment initiatives, train tardiness, rail safety and security as well as poor. Here are some of the obstacles encountered in the PT.KAI employees to improve performance.This study aimed to determine the effect of transformational leadership and motivation on employee performance. The sample of this research is 82 respondents employees of PT. KAI DAOP IV Semarang. Data analysis was performed using multiple linear regression, t test, F test, and adjusted R².Based on the analysis concluded that transformational leadership and motivational variables may affect the performance of the variable employee at PT KAI Daop IV Semarang. Formed regression equation is: Y = 0.515X1 + 0.473 X2. Based on the analysis of data on 82 of the respondents, on the performance of employees in PT.KAI Daop IV Semarang, can be summed up as follows: Variable of transformational leadership can affect the performance of employees at PT KAI Daop IV Semarang. The better the implementation of transformational leadership results in improved employee performance. Motivational variables may affect the variable performance of employees at PT. KAI Daop IV Semarang. It is characterized by the presence of the positive effect of motivation on employee performance variables. The higher the motivation given to employees resulting in higher employee performance.